Kadar Polifenol Total Ekstrak Etanol Kulit Buah Manggis (Garcinia mangostana) Pada Variasi Asal Daerah - Any Guntarti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background:Mangosteen peel is one of the waste of mangosteen, that nowadays have already utilized much to manage health problems. One of the ingredients in the mangosteen fruit skin is a polyphenols. Objective: to determine the polyphenols content of the ethanol extract of mangosteen peel variations based on different regions. Methods: Powder of dried mangosteen peel that come from 3 difference areas, Sumatera (Pekanbaru), Jawa (Yogyakarta) and Kalimantan (Martapura) extracted with ethanol 70% by multilevel maceration. Extract that obtained than tested specific parameter form of qualitative test of polyphenols compounds with FeCl3, AlCl3, ammonia vapor, Folin Ciucalteau and tannin test. Determination level of polyphenols (Gallic acid) with visible spectrophotometri after reacted with Folin Ciucalteau reagent. Results: The result of this research was quality test of extract etanol 70% Specific parameter test total phenol content (mg GAE/g ekstrak) from Sumatera, Jawa and Kalimantan are :824.13 (mg GAE/g ekstrak); 155,86 (mg GAE/g ekstrak); 688,9 (mg GAE/g ekstrak). Conclusions: There were difference in contents of polyphenol of mangosteen peel origin among Sumatera, Jawa and Kalimantan.